Energy Consumption and Potential Savings in the Automotive Body Shop - Kadhim, Rafid; Norin, Albert (My University, 2021)
Extensive effort has been put into measuring sustainability efficiency within the manufacturing over the last few years. This study presents a comprehensive look at sustainability solutions within the industry and further development of an existing energy map. It is vital that existing buildings operate more efficiently while providing a lower impact on the environment, and it is essential that new structures maximize their energy efficiency. The ventilation system of a building accounts for a significant portion of its energy consumption, and there is frequently significant potential for the system to be optimized and streamlined. This report consists of the end result of an evaluation of the usage of sustainability evaluation techniques inside the industry. This through a literature study and meetings with experienced individuals from each relevant sector. Based on our analysis, a conclusion could be drawn that the possibilities for a more environmentally friendly and efficient system were possible and profitable for the case company when making changes to their lighting situation such as changing to LED lights and also making the heat exchangers more effective by establish a regular maintenance schedule against the so called "Fouling effect". Furthermore, when working with the effectiveness of the heat exchangers calculations were made to obtain a value, this value showed the potential amount of heat that could be recovered from the given system. Some suggestions were proposed to the case company on where this obtained value could be used in future research. In order to promote sustainable production, industry and academia must collaborate on method creation and implementation. Also, collaboration between industries must be implemented, because the case company must show a sense of responsibility and understand that sustainability is not a competition-oriented topic.
Keywords: Sustainable energy systems, energy research, energy optimization; heating, lights